INTERNET JOURNALISM AS AN IMPORTANT COMPONENT OF THE MODERN MASS INFORMATION SYSTEM PR - Murtozayeva Nigora Murtoza Qizi (International Journal of Literature and Language Studies, 2026)
PR (Public relations) has become an important component of the modern mass information system of internet journalism, fundamentally changing the processes of information production and distribution. Under the influence of PR, journalism activities are advancing not only socially but also practically to a new stage. In this process, PR relations are rapidly developing and manifesting as important factors that determine the content and functional direction of internet journalism based on the principles of populism.